Capabilities and social capital in the face of natural hazards in the elderly: the case of the Nevados de Chillán Volcanic Complex, Chile - Sandoval Díaz, José Sebastian; Monsalves Peña , Saron; Vejar Valles, Vivana (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Chile has a high level of exposure and vulnerability to disaster risk processes and is also one of the five countries with the highest number of active volcanoes in the world. In addition to this scenario, there is a sustained increase in the aging population, which is a highly vulnerable age group in the face of natural hazards. However, previous experiences, local contexts and organizations can provide opportunities for older people to acquire and deploy adaptive coping skills in critical situations. For this reason, the present study analyzed the individual and collective capacities of older people exposed to volcanic risk in a rural area of southern Chile. A qualitative, phenomenological case design was used, and 15 elderly people were purposively selected. The collected data is produced through semi-structured interviews and a focus group, using the grounded theory coding process as an analysis strategy. As a first result, psychological resilience, positive aging and mobilization in the face of volcanic risk are identified as individual coping capacities. In terms of collective capacities, the role of social capital is identified as the presence of community and institutional links and organizational networks that facilitate processes of participation, involvement, trust and solidarity at the local level. In conclusion, the importance of incorporating the capacity for agency and positive aging in local disaster risk management is sustained, understanding that the strengthening of adaptation and resilience must be combined with participation and structural and institutional reduction of vulnerabilities.